TEKNIK PELAKSANAAN SUPERVISI DALAM MEMBENTUK KOMPETENSI PROFESIONALITAS GURU - Tri Lestari; Binti Maunah; Prim Masrokan Mutohar (Program Studi Manajemen Pendidikan Islam, 2022)
Supervision is an important service provided to teachers with the aim of improving the quality of the teaching staff. The implementation of supervision is very important to be carried out by the principal in order to develop the professionalism of the teacher himself. Teachers who are the spearhead of the success of an education are required to work professionally. Therefore, to make teachers professional, one of the efforts is to carry out supervision, both by the principal and supervisor. In carrying out supervision, supervisors are expected not to act as supervisors who are only looking for teachers in carrying out their duties. On the other hand, supervisors must be able to provide service assistance to overcome problems faced by teachers. Therefore, supervisors must be able and understand and master the objectives, techniques, functions as well as supervision methods, in order to obtain optimal benefits in the form of professional teachers.